A network architect's guide to 5G - Hassan, Syed Farrukh; Orel, Alexander; Islam, Kashif (Addison-Wesley, 2022)
As 5G transforms mobile usage and services, network professionals will need to significantly evolve their transport network architectures towards greater sophistication and stronger integration with radio networks, and facilitate transition towards cloud-native 5G mobile core. Until now, however, most 5G guides have foregrounded RF/radio and mobile core innovations, not its implications for data networks. A Network Architects Guide to 5G fills the gap, giving network architects, designers, and engineers essential knowledge for designing and planning their own 5G networks. Drawing on decades of experience with global service providers and enterprise networks, the authors illuminate new and evolving network technologies necessary for building 5G-capable networks, such as segment routing, network slicing, timing and synchronization, edge computing, distributed data centers, integration with public cloud, and more. They explain how 5G blurs boundaries between mobile core, radio access, and transport, as well as the changes in the composition of a traditional cell site with the adoption of Open and Virtualized RAN resulting in a transition to mobile xHaul. Every chapter builds on earlier coverage, culminating in a big picture presentation of a complete 5G network design.